Frontline community health care workers' intervention for diabetes management in resource limited settings: a qualitative study on perspectives of key stakeholders. (2021) - Poobalan, Amudha; Whiteley, Emma; Balsubramanya, Bhavya; Philip, Sam; Jebaraj, Paul; BV, Balaji; John, Oommen; Thomas, Nihal; Abraham, Prakash; Isaac, Rita
No abstract available